Variability of cork from Portuguese Quercus suber studied by solid-state 13C-NMR and FTIR spectroscopies - Lopes, M. H.; Barros, A. S.; Pascoal Neto, C.; Rutledge, D.; Delgadillo, I.; Gil, A. M. (Biopolymers, 2001)
A new approach is presented for the study of the variability of Portuguese reproduction cork using solid-state 13C-NMR spectroscopy and photoacoustic (PAS) FTIR (FTIR-PAS) spectroscopy combined with chemometrics. Cork samples were collected from 12 different geographical sites, and their 13C-cross-polarization with magic angle spinning (CP/MAS) and FTIR spectra were registered. A large spectral variability among the cork samples was detected by principal component analysis and found to relate to the suberin and carbohydrate contents. This variability was independent of the sample geographical origin but significantly dependent on the cork quality, thus enabling the distinction of cork samples according to the latter property. The suberin content of the cork samples was predicted using multivariate regression models based on the 13C-NMR and FTIR spectra of the samples as reported previously. Finally, the relationship between the variability of the 13C-CP/MAS spectra with that of the FTIR-PAS spectra was studied by outer product analysis. This type of multivariate analysis enabled a clear correlation to be established between the peaks assigned to suberin and carbohydrate in the FTIR spectrum and those appearing in the 13C-CP/MAS spectra. © 2001 John Wiley & Sons, Inc. Biopolymers (Biospectroscopy) 62: 268–277, 2001
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Inc.
Keywords: 13C-cross-polarization with magic angle spinning; chemometrics; Cork; outer product analysis; photoacoustic FTIR; Quercus suber Linnaeus

Quantitation of aliphatic suberin in Quercus suber L. cork by FTIR spectroscopy and solid-state 13C-NMR spectroscopy - Lopes, M. H.; Neto, C. Pascoal; Barros, A. S.; Rutledge, D.; Delgadillo, I.; Gil, A. M. (Biopolymers, 2000)
This work determined that the percentage of suberin in cork may be found by solid-state 13C cross polarization/magic angle spinning (CP/MAS) NMR spectroscopy and by FTIR with photoacoustic detection (FTIR-PAS) spectroscopy. A linear relationship is found between the suberin content measured through CP/MAS spectral areas and that measured gravimetrically. Furthermore, application of a partial least squares (PLS1) regression model to the NMR and gravimetric data sets clearly correlates the two sets, enabling suberin quantification with 90% precision. Suberin quantitation by FTIR-PAS spectroscopy is also achieved by a PLS1 regression model, giving 90% accurate estimates of the percentage of suberin in cork. Therefore, 13C-CP/MAS NMR and FTIR-PAS proved to be useful and accurate noninvasive techniques to quantify suberin in cork, thus avoiding the traditional time consuming and destructive chemical methods. © 2000 John Wiley & Sons, Inc. Biopolymers (Biospectroscopy) 57: 344–351, 2000
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Inc.
Keywords: 13 C-cross polarization/ magic angle spinning; Cork; FTIR spectroscopy with photoacoustic detection; multivariate calibration; quantitation; Quercus suber L.; solid-state NMR; suberin

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy